In-situ MOF-74 derived carbon coating for graphite surface and preparation method of in-situ MOF-74 derived carbon coating
By preparing in-situ MOF-74 derived carbon coating on the graphite surface, the problems of the influence of binder impurities and insufficient wear resistance of graphite products are solved, and the effect of improving the service life of graphite products and building a self-support electrode is achieved.
Patent Information
- Application Number
- CN202411899633.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art has the influence of impurities such as binders in the surface modification of graphite, and the wear resistance of graphite products under working conditions is insufficient and their service life is short.
The MOF-74-derived carbon coating was prepared on the graphite surface by in situ growth-carbonization, and metal zinc was prepared by electrochemical deposition and liquid phase reaction, and then bonded with the 2,5-dihydroxyterephthalic acid ligand, and pyrolyzed carbonization at high temperature to form a mesoporous hard carbon coating.
This method avoids the use of impurities such as binders, significantly improves the wear resistance of graphite products under working conditions, extends service life, and constructs a mesoporous carbon self-supporting electrode without using binders.
Smart Images

Figure CN119684037A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphite materials, and in particular to an in-situ MOF-74 derived carbon coating for a graphite surface and a preparation method thereof. Background Art
[0002] MOF-derived carbon materials are carbon materials obtained by converting metal organic framework (MOF) materials. MOF is a type of three-dimensional structured material composed of metal ions or metal clusters and organic ligands through coordination bonds, and has a highly ordered pore structure. Carbon materials with excellent performance can be obtained by subjecting MOF materials to high-temperature carbonization or pyrolysis. The highly adjustable pore structure of MOF can be retained or converted into pores in the carbon material. At the same time, the carbon material obtained after high-temperature pyrolysis has good thermal stability and chemical stability, and is suitable for application in harsh environments. In addition, MOF-derived carbon materials can simultaneously have multiple functions such as adsorption, catalysis, conductivity, and energy storage. Mesoporous carbon materials have a large pore size range (usually between 2-50nm) and have attracted much attention in the fields of adsorption, catalysis and energy storage in recent years. Mesoporous carbon materials usually have a large specific surface area, which helps to provide more adsorption sites and enhance the adsorption capacity of various molecules (such as gases, ions, organic pollutants, etc.). The pore size of mesoporous carbon materials is moderate, which can effectively accommodate molecules and promote the diffusion of molecules in the pores, thereby improving the adsorption rate and efficiency. Self-supporting electrodes or binder-free electrode materials refer to an electrode design that does not use a binder as a material in the electrodes of energy storage devices such as batteries or supercapacitors. In traditional electrode materials, binders are usually used to bind active materials together and combine with conductive materials (such as carbon black), but binder-free electrode materials do not rely on these polymer binders. Binders are usually non-conductive, so they increase the internal resistance of the electrode and reduce the conductivity. In binder-free electrodes, the conductivity of the electrode can be improved due to the absence of these non-conductive substances. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide an in-situ MOF-74 derived carbon coating for graphite surface and a preparation method thereof, which adopts an in-situ growth-carbonization method to avoid the use of binders, thickeners, other solvents, etc., and reduce the impact of impurities brought by them on the final product; it can enhance the wear resistance of graphite products under working conditions, which is beneficial to improve the service life of graphite products; when applied to the surface modification of graphite electrodes, the in-situ formed carbon coating can construct a mesoporous carbon self-supporting electrode without the use of a binder.
[0004] Technical solution: An in-situ MOF-74 derived carbon coating for graphite surface, wherein the MOF-74 derived carbon coating is a carbon coating formed by high-temperature graphitization of the in-situ MOF-74 coating; wherein the in-situ MOF-74 coating is prepared by liquid phase reaction of metallic zinc electrochemically deposited on the graphite surface in a methanol solution of 2,5-dihydroxyterephthalic acid. The method for preparing the in-situ MOF-74 derived carbon coating on the graphite surface comprises the following steps: Step 1: Clean the porous graphite substrate with acetone, alcohol and water and dry it; Step 2: depositing metallic zinc on the surface of a porous graphite substrate by an electrochemical deposition method, wherein the electrolyte is an aqueous solution of zinc chloride, and the deposition method adopts constant current deposition, wherein the density of metallic zinc deposition is controlled by the magnitude of the current density. As the current density increases, metallic zinc is more inclined to nucleate at multiple points on the graphite surface, thereby increasing the density of metallic zinc deposition; controlling the amount of metallic zinc deposition by the deposition capacity surface density, i.e., the product of the current density and the deposition time, thereby regulating the in-situ growth of MOF-74 on the graphite surface in the subsequent steps; the longer the deposition time at the same current density, the greater the thickness of the deposited metallic zinc layer, and the greater the thickness of the subsequent in-situ grown MOF-74 coating; after completion, washing with water and vacuum drying at 60° C. to obtain a graphite sheet with a galvanized surface; Step 3: Soak the zinc-plated graphite sheet in a methanol solution of 2,5-dihydroxyterephthalic acid for 15 to 60 minutes, dissolve the zinc on the surface of the graphite sheet into zinc ions and bond with the 2,5-dihydroxyterephthalic acid ligands to in-situ grow a MOF-74 coating on the surface of the graphite sheet, wash it alternately with methanol and water and dry it to obtain a graphite sheet with in-situ growth of MOF-74 on the surface; adjust the concentration of the methanol solution of 2,5-dihydroxyterephthalic acid to adjust the formation of MOF-74. The nucleation rate is increased to regulate the size of MOF-74 particles. As the concentration of the methanol solution of 2,5-dihydroxyterephthalic acid increases, the nucleation rate increases, and the MOF-74 particles become smaller. Step 4: Under an inert atmosphere such as nitrogen and argon, the graphite sheet with MOF-74 in situ grown on the surface is subjected to high-temperature pyrolysis and carbonization to form granular mesoporous hard carbon, thereby achieving in-situ coating of the mesoporous hard carbon on the surface of the graphite sheet, thereby obtaining an in-situ MOF-74-derived carbon coating for the graphite surface. Furthermore, the mass fraction of zinc chloride in the zinc chloride aqueous solution in step 2 is 30%. Furthermore, the constant current deposition condition in step 2 is a current density of 0.05 to 0.5 A / cm 2 , the deposition time is 10 to 30 minutes. Further, in step 3, the concentration of the methanol solution of 2,5-dihydroxyterephthalic acid is 0.02 to 0.1 g / mL. Beneficial effects: 1. The present invention adopts the in-situ growth-carbonization method, avoiding the use of binders, thickeners, other solvents, etc., and reducing the impact of impurities brought by them on the final product; 2. The in-situ MOF-74 derived carbon coating of the present invention can enhance the wear resistance of graphite products under working conditions, which is beneficial to improving the service life of graphite products; 3. When the in-situ MOF-74 derived carbon coating of the present invention is applied to the surface modification of graphite electrodes, the in-situ formed carbon coating can construct a self-supporting electrode without using a binder; 4. The MOF-74 material involved in the in-situ MOF-74 derived carbon coating of the present invention contains only carbon, hydrogen, oxygen and zinc elements. After the high-temperature graphitization process, only carbon elements exist, and no other element impurities are introduced into the graphite product; 5. The MOF-74 particles prepared by this method have a high specific surface area after carbonization, and the pore structure is dominated by mesopores. The mesoporous structure has excellent performance in the fields of material adsorption, electrochemical energy storage, and electrocatalysis; 6. The chemical reaction involved in the present invention has high reaction activity, rapid reaction and mild conditions, and the scheme is easy to implement, and has good application potential in production. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1The present invention is a flow chart for preparing an in-situ MOF-74 derived carbon coating on a graphite surface; Figure 2 This is a scanning electron microscope image of the metal zinc on the surface of the graphite sheet after surface galvanizing obtained in step 2 of Example 1; Figure 3 This is a scanning electron microscope image of MOF-74 on the surface of a graphite sheet with MOF-74 in situ grown on the surface obtained in step 3 of Example 1. DETAILED DESCRIPTION Example 1 A method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface comprises the following steps: Step 1: Clean the porous graphite substrate with acetone, alcohol and water and dry it; Step 2: Electrochemical deposition is used to deposit metallic zinc on the surface of the porous graphite substrate. The electrolyte is a 30% zinc chloride aqueous solution. The deposition method is constant current deposition with a current density of 0.05 A / cm 2 The deposition time is 20 min, after which the surface is washed with water and dried in vacuum at 60 °C to obtain a graphite sheet with a zinc-plated surface; Step 3: Soak the zinc-plated graphite sheet in a methanol solution of 2,5-dihydroxyterephthalic acid at a concentration of 0.1 g / mL for 15 minutes, so that the zinc on the surface of the graphite sheet dissolves into zinc ions and bonds with the 2,5-dihydroxyterephthalic acid ligands to in-situ grow a MOF-74 coating on the surface of the graphite sheet, and then wash and dry the sheet alternately with methanol and water to obtain a graphite sheet with in-situ growth of MOF-74 on the surface; Step 4: Under an inert atmosphere such as nitrogen or argon, the graphite sheet with MOF-74 in situ grown on the surface is subjected to high-temperature pyrolysis and carbonization to form granular mesoporous hard carbon, thereby achieving in-situ coating of the mesoporous hard carbon on the surface of the graphite sheet, thereby obtaining an in-situ MOF-74-derived carbon coating for the graphite surface. Example 2 A method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface comprises the following steps: Step 1: Clean the porous graphite substrate with acetone, alcohol and water and dry it; Step 2: Deposit metallic zinc on the surface of the porous graphite substrate by electrochemical deposition. The electrolyte is a 30% zinc chloride aqueous solution. The deposition method uses constant current deposition with a current density of 0.2 A / cm 2 The deposition time is 20 min, after which the surface is washed with water and dried in vacuum at 60 °C to obtain a graphite sheet with a zinc-plated surface; Step 3: Soak the zinc-plated graphite sheet in a methanol solution of 2,5-dihydroxyterephthalic acid at a concentration of 0.1 g / mL for 15 minutes, so that the zinc on the surface of the graphite sheet dissolves into zinc ions and bonds with the 2,5-dihydroxyterephthalic acid ligands to in-situ grow a MOF-74 coating on the surface of the graphite sheet, and then wash and dry the sheet alternately with methanol and water to obtain a graphite sheet with in-situ growth of MOF-74 on the surface; Step 4: Under an inert atmosphere such as nitrogen or argon, the graphite sheet with MOF-74 in situ grown on the surface is subjected to high-temperature pyrolysis and carbonization to form granular mesoporous hard carbon, thereby achieving in-situ coating of the mesoporous hard carbon on the surface of the graphite sheet, thereby obtaining an in-situ MOF-74-derived carbon coating for the graphite surface. Example 3 A method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface comprises the following steps: Step 1: Clean the porous graphite substrate with acetone, alcohol and water and dry it; Step 2: Deposit metallic zinc on the surface of the porous graphite substrate by electrochemical deposition. The electrolyte is a 30% zinc chloride aqueous solution. The deposition method uses constant current deposition with a current density of 0.1 A / cm 2 The deposition time was 10 min, after which the surface was washed with water and dried in vacuum at 60 °C to obtain a graphite sheet with a zinc-plated surface; Step 3: Soak the zinc-plated graphite sheet in a methanol solution of 2,5-dihydroxyterephthalic acid at a concentration of 0.02 g / mL for 15 minutes, so that the zinc on the surface of the graphite sheet dissolves into zinc ions and bonds with the 2,5-dihydroxyterephthalic acid ligands to in-situ grow a MOF-74 coating on the surface of the graphite sheet, and then wash and dry the sheet alternately with methanol and water to obtain a graphite sheet with MOF-74 in-situ grown on the surface; Step 4: Under an inert atmosphere such as nitrogen or argon, the graphite sheet with MOF-74 in situ grown on the surface is subjected to high-temperature pyrolysis and carbonization to form granular mesoporous hard carbon, thereby achieving in-situ coating of the mesoporous hard carbon on the surface of the graphite sheet, thereby obtaining an in-situ MOF-74-derived carbon coating for the graphite surface. Example 4 A method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface comprises the following steps: Step 1: Clean the porous graphite substrate with acetone, alcohol and water and dry it; Step 2: Deposit metallic zinc on the surface of the porous graphite substrate by electrochemical deposition. The electrolyte is a 30% zinc chloride aqueous solution. The deposition method uses constant current deposition with a current density of 0.1 A / cm 2 The deposition time was 30 min, after which the surface was washed with water and dried in vacuum at 60 °C to obtain a graphite sheet with a zinc-plated surface; Step 3: Soak the zinc-plated graphite sheet in a methanol solution of 2,5-dihydroxyterephthalic acid at a concentration of 0.02 g / mL for 30 minutes, so that the zinc on the surface of the graphite sheet dissolves into zinc ions and bonds with the 2,5-dihydroxyterephthalic acid ligands to in-situ grow a MOF-74 coating on the surface of the graphite sheet, and then wash and dry the sheet alternately with methanol and water to obtain a graphite sheet with MOF-74 in-situ grown on the surface; Step 4: Under an inert atmosphere such as nitrogen or argon, the graphite sheet with MOF-74 in situ grown on the surface is subjected to high-temperature pyrolysis and carbonization to form granular mesoporous hard carbon, thereby achieving in-situ coating of the mesoporous hard carbon on the surface of the graphite sheet, thereby obtaining an in-situ MOF-74-derived carbon coating for the graphite surface. Example 5 A method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface comprises the following steps: Step 1: Clean the porous graphite substrate with acetone, alcohol and water and dry it; Step 2: Deposit metallic zinc on the surface of the porous graphite substrate by electrochemical deposition. The electrolyte is a 30% zinc chloride aqueous solution. The deposition method uses constant current deposition with a current density of 0.1 A / cm 2 The deposition time is 20 min, after which the surface is washed with water and dried in vacuum at 60 °C to obtain a graphite sheet with a zinc-plated surface; Step 3: Soak the zinc-plated graphite sheet in a methanol solution of 2,5-dihydroxyterephthalic acid at a concentration of 0.02 g / mL for 20 minutes, so that the zinc on the surface of the graphite sheet dissolves into zinc ions and bonds with the 2,5-dihydroxyterephthalic acid ligands to in-situ grow a MOF-74 coating on the surface of the graphite sheet, and then wash and dry the sheet alternately with methanol and water to obtain a graphite sheet with in-situ growth of MOF-74 on the surface; Step 4: Under an inert atmosphere such as nitrogen or argon, the graphite sheet with MOF-74 in situ grown on the surface is subjected to high-temperature pyrolysis and carbonization to form granular mesoporous hard carbon, thereby achieving in-situ coating of the mesoporous hard carbon on the surface of the graphite sheet, thereby obtaining an in-situ MOF-74-derived carbon coating for the graphite surface. Example 6 A method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface comprises the following steps: Step 1: Clean the porous graphite substrate with acetone, alcohol and water and dry it; Step 2: Deposit metallic zinc on the surface of the porous graphite substrate by electrochemical deposition. The electrolyte is a 30% zinc chloride aqueous solution. The deposition method uses constant current deposition with a current density of 0.1 A / cm 2 The deposition time is 20 min, after which the surface is washed with water and dried in vacuum at 60 °C to obtain a graphite sheet with a zinc-plated surface; Step 3: Soak the zinc-plated graphite sheet in a methanol solution of 2,5-dihydroxyterephthalic acid at a concentration of 0.05 g / mL for 20 minutes, so that the zinc on the surface of the graphite sheet dissolves into zinc ions and bonds with the 2,5-dihydroxyterephthalic acid ligands to in-situ grow a MOF-74 coating on the surface of the graphite sheet, and then wash and dry the sheet alternately with methanol and water to obtain a graphite sheet with MOF-74 in-situ grown on the surface; Step 4: Under an inert atmosphere such as nitrogen or argon, the graphite sheet with MOF-74 in situ grown on the surface is subjected to high-temperature pyrolysis and carbonization to form granular mesoporous hard carbon, thereby achieving in-situ coating of the mesoporous hard carbon on the surface of the graphite sheet, thereby obtaining an in-situ MOF-74-derived carbon coating for the graphite surface. Comparative Example 1 The difference between this comparative example and Example 1 is that the epoxy resin is coated on the surface of the graphite sheet by a brushing method, and the graphite sheet with an epoxy resin-derived hard carbon coating is obtained by high-temperature carbonization. The specific preparation method is as follows: Step 1: Mix E51 epoxy resin and curing agent in a ratio of 70:30, and evenly apply it on the surface of the cleaned and dried graphite sheet, and cure it at 120℃ for 4h. The coating amount of epoxy resin is 0.05g / cm 2 ; Step 2: The graphite sheet obtained in step 1 is heat treated at 1100° C. for 2 h under inert gas protection to obtain a graphite sheet with epoxy resin-derived hard carbon. Comparative Example 2 The difference between this comparative example and Example 1 is that a hard carbon coating is prepared on the surface of a graphite sheet by a conventional brushing method, using ZIF-8 as a precursor and epoxy resin as a binder. The preparation method comprises the following steps: Step 1: Dissolve 9.87 mmol of zinc nitrate hexahydrate and 79.4 mmol of 2-methylimidazole in 200 mL of methanol respectively; under stirring, quickly pour the zinc nitrate hexahydrate solution into 2-methylimidazole, stir at room temperature for 1 hour, centrifuge at 12000 rpm, wash with methanol 4 times, and vacuum dry at 60°C for 12 hours to obtain ZIF-8; Step 2: Mix the ZIF-8 obtained in step 1 with E51 epoxy resin in a mass ratio of 1:10. After mixing evenly, add curing agent, and the ratio of epoxy resin to curing agent is 70:30. Mix evenly again and apply it evenly on the surface of the cleaned and dried graphite sheet, and cure it at 120°C for 4h. The coating amount of the mixture is 0.06g / cm 2 ; Step 3: The graphite sheet obtained in step 2 is heat treated at 1100° C. for 2 h under inert gas protection to obtain a graphite workpiece with ex-situ ZIF-8 derived hard carbon. Comparative Example 3 The difference between this comparative example and Example 1 is that a hard carbon coating is prepared on the surface of a workpiece by a conventional brushing method, using MOF-74 particles as a precursor and epoxy resin as a binder. The preparation method comprises the following steps: Step 1: Dissolve 4 mmol of zinc acetate dihydrate and 1.5 mmol of 2,5-dihydroxyterephthalic acid in 100 mL and 50 mL of methanol, respectively; add the 2,5-dihydroxyterephthalic acid solution dropwise to the zinc acetate dihydrate solution under stirring, stir at room temperature for 2 h, centrifuge at 12000 rpm, wash with methanol 4 times, and vacuum dry at 60 ° C for 12 h to obtain MOF-74 particles; Step 2: Mix the MOF-74 obtained in step 1 with E51 epoxy resin in a mass ratio of 1:10. After mixing evenly, add curing agent, and the ratio of epoxy resin to curing agent is 70:30. Mix evenly again and apply it evenly on the surface of the cleaned and dried graphite sheet, and cure it at 120°C for 4h. The coating amount of the mixture is 0.06g / cm 2 ; Step 3: The graphite sheet obtained in step 2 is heat treated at 1100° C. for 2 h under inert gas protection to obtain a graphite sheet with ex-situ MOF-74 derived hard carbon. Performance Testing 1. Specific surface area test, reference standard "GB / T 19587-2017" The surface coating of the graphite workpiece in each embodiment and the comparative example was mechanically peeled off by using a scraper, and the specific surface area and the proportion of mesopores were analyzed by using a fully automatic BET specific surface analysis tester. 2. Tensile test required to destroy the coating, refer to the standard "GB / T 5210-2006" The adhesion test of the pull-off method was used to measure and evaluate the bonding strength and wear resistance of the coatings in Examples 1-6 and this comparative example. The test column was bonded to the coating surface with an adhesive. After the adhesive was cured, the bonded experimental combination was placed on a suitable pressure testing machine. The bonded experimental combination was subjected to a controllable tensile test to measure the tensile force required to destroy the coating / substrate, and the experimental results were expressed by the magnitude of the tensile force that destroyed the coating. 3. Coating thickness test: Observe the coating thickness under a scanning electron microscope The results are shown in Table 1. The in-situ MOF-74 derived hard carbon has a mass of 1600 m 2 / g or more, and the mesopore ratio is higher than 80%, both of which are higher than those of epoxy resin and ZIF-8 derived hard carbon coatings. In addition, in-situ coating effectively improves the bonding of the coating and makes it easier to achieve uniform coating of small thickness coatings. Table 1
Claims
1. An in-situ MOF-74 derived carbon coating for graphite surface, characterized in that: The MOF-74 derived carbon coating is a carbon coating formed by high-temperature carbonization of an in-situ MOF-74 coating; wherein the in-situ MOF-74 coating is prepared by liquid phase reaction of metal zinc electrochemically deposited on the graphite surface in a methanol solution of 2,5-dihydroxyterephthalic acid.
2. The method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface according to claim 1, characterized in that: The following steps are involved: Step 1: Clean the porous graphite substrate with acetone, alcohol and water and dry it; Step 2: depositing metallic zinc on the surface of the porous graphite substrate by electrochemical deposition, wherein the electrolyte is a zinc chloride aqueous solution, and the deposition method adopts constant current deposition, and then washing with water and vacuum drying at 60° C. to obtain a graphite sheet with a zinc-plated surface; Step 3: Soak the zinc-plated graphite sheet in a methanol solution of 2,5-dihydroxyterephthalic acid for 15 to 60 minutes, so that the zinc on the surface of the graphite sheet dissolves into zinc ions and bonds with the 2,5-dihydroxyterephthalic acid ligands to in-situ grow a MOF-74 coating on the surface of the graphite sheet, and then wash and dry the sheet alternately with methanol and water to obtain a graphite sheet with in-situ growth of MOF-74 on the surface; Step 4: Under an inert atmosphere such as nitrogen or argon, the graphite sheet with MOF-74 in situ grown on the surface is subjected to high-temperature pyrolysis and carbonization to form granular mesoporous hard carbon, thereby achieving in-situ coating of the mesoporous hard carbon on the surface of the graphite sheet, thereby obtaining an in-situ MOF-74-derived carbon coating for the graphite surface.
3. The method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface according to claim 2, characterized in that: The mass fraction of zinc chloride in the zinc chloride aqueous solution in step 2 is 30%.
4. The method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface according to claim 2, characterized in that: The constant current deposition condition in step 2 is a current density of 0.05 to 0.5 A / cm 2 , the deposition time is 10 to 30 minutes.
5. The method for preparing an in-situ MOF-74 derived carbon coating on a graphite surface according to claim 2, characterized in that: In step 3, the concentration of the methanol solution of 2,5-dihydroxyterephthalic acid is 0.02-0.1 g / mL.